PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KOMITMEN ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN: (Studi pada Puskesmas Kalibawang, Kabupaten Kulon Progo) - Dwi Novitasari; Fidiastuti Fidiastuti (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2018)
The purpose of this study is to examine the effect of transformational leadership, organizational commitment, and job satisfaction on employee performance at Puskesmas Kalibawang, Kulon Progo. This research is a causal associative with quantitative approach. The data obtained by primary data using questionnaire method. Hypothesis testing in this reasearch are multiple linear regression analysis, F-test and T-test used to examined research model and determine the effect of independent variables to the dependent variable. The results showed a positive and significant effect of transformational leadership, organizational commitment, and job satisfaction on employee performance (sig. 0,000 less than 0.05). T-test showed no effect of transformational leadership on employee performance (sig. 0,844 greather than 0,05). Organizational commitment has positive and significant effect on employee performance (sig. 0,011 less than 0,05) and job satisfaction also have positive and significant effect to employee performance (sig. 0,032 less than 0,05).